Early Initiation of Dangle Protocol in Lower Extremity Free Flap Microsurgery - Su, Shannon; Menon, Ambika; Taillon, Carolyn; Saad, Omar; Merceron, Tyler; Ghareeb, Paul (Journal of Reconstructive Microsurgery, 2025)
Defects of the lower extremity often require free tissue transfer to provide adequate soft tissue reconstruction. Patients typically undergo a postoperative dangle protocol to condition the flap to withstand the increase in venous pressure. The purpose of this study was to evaluate the safety and postoperative length of stay after early initiation of dangle.A retrospective review of patients undergoing lower extremity free tissue transfer reconstruction at the Grady Memorial Hospital from 2012 to 2022 was conducted. Patient demographics, surgical characteristics, and outcomes were analyzed. Patients were categorized into two groups: early (within 5 days after surgery) and late dangle (day 6 or greater). Univariate and multivariate statistical analyses were performed, with significance determined to be p < 0.05.A total of 83 of 99 available patients met inclusion criteria; 22 patients underwent early and 61 late dangle. Free flap survival was 90.9% in the early and 90.2% in the late group. The mean postoperative length of stay in the early and late groups were 12.3 and 18.8 days, respectively (p = 0.0018). There was no difference in the number of patients who had wound healing complications, flap failure, and a need for amputation in each group.Our results demonstrate that initiation of an early dangle protocol does not affect surgical outcome and leads to a reduction in postoperative length of stay. These results can be used to inform evidence-based recommendations for flap management in lower extremity reconstruction.
Keywords: dangle protocol; free flap; outcomes